2016
DOI: 10.4084/mjhid.2016.039
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal therapy in hematopoietic stem cell transplant recipients

Abstract: Invasive fungal infections (IFI) represent a major hindrance to the success of hematopoietic stem cell transplantation (HSCT), contributing substantially to morbidity and infection-related mortality. During the most recent years several reports indicate an overall increase of IFI among hematologic patients, in particular, invasive aspergillosis, that may be explained, at least partially, by the fact that diagnoses only suspected in the past, are now more easily established due to the application of serum bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…[ 8 ] Transplantation-associated morbidity and mortality rates have declined significantly in recent years due to advances in transplantation medicine with tailored conditioning regimens, precise HLA (human-leucocyte-antigen) -typing, improved supportive therapy, and prophylaxis against severe infections. [ 9 ] Further reduction of the complication rate to improve outcomes following HSCT requires detailed therapy and follow-up care protocols tailored to each patient’s risk factors. Our relatively heterogeneous patient collective reflects real pediatric oncological clinical practice in use of stem cell transplantation.…”
Section: Introduction / Backgroundmentioning
confidence: 99%
“…[ 8 ] Transplantation-associated morbidity and mortality rates have declined significantly in recent years due to advances in transplantation medicine with tailored conditioning regimens, precise HLA (human-leucocyte-antigen) -typing, improved supportive therapy, and prophylaxis against severe infections. [ 9 ] Further reduction of the complication rate to improve outcomes following HSCT requires detailed therapy and follow-up care protocols tailored to each patient’s risk factors. Our relatively heterogeneous patient collective reflects real pediatric oncological clinical practice in use of stem cell transplantation.…”
Section: Introduction / Backgroundmentioning
confidence: 99%
“…Antibiotics are extremely important in transplantation and regenerative medicine procedures. Isolation and cultivation of adipose-derived stem cells usually involves the presence of the penicillin-streptomycin mixture [ 2 , 5 , 8 , 9 ] although some studies have also suggested using amphotericin B because of its widespread antifungal activity [ 10 , 11 ]. Gentamycin is also commonly used in cell cultures, although a penicillin-streptomycin (PS) mixture is the only one that is recommended by the American Type Culture Collection (ATCC) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gentamycin is also commonly used in cell cultures, although a penicillin-streptomycin (PS) mixture is the only one that is recommended by the American Type Culture Collection (ATCC) [ 12 ]. Protective/preventive antibiotic therapy improves the success/safety of transplantation procedures [ 10 ]. To minimize complications, stem cells must be isolated and cultured under the optimal conditions for a particular cell type, in order to use them in transplantology.…”
Section: Introductionmentioning
confidence: 99%
“…This risk score may have important implications to tailor antifungal prophylaxis in our patients, especially in those with one or more RFs who may benefit from other prophylaxis (posaconazole or isavuconazole). 44 Importantly, we also identified a very low-risk subgroup of UCBT recipients in whom we can speculate that such a group may not require antimold prophylaxis at all. Despite appropriate antifungal therapy, we report 6-and 12-week mortality rates of 36% Among IYDs, we found that candidemia was the most common event characterized by its early presentation (50% occurred before engraftment) which is consistent with recent experiences.…”
Section: Discussionmentioning
confidence: 78%